(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2017)
In this paper is presented and discussed the hypothesis of a particular form of intelligence, in the context of the theories on the multiple intelligences: the “graphic intelligence”, intended as the capacity to use the drawing skills and, more generally, the ability to integrate the use of eye, mind and hand to solve problems and to create effective products aimed to acquiring new knowledge. Indeed, the recent research from the cognitive sciences suggests the existence of meaningful relationship between graphic representation and cognitive development that could support the idea of a graphic intelligence autonomous from other forms of intelligence which have until now been considered capable of describing and comprehend this type of human intellectual competence. Thus, the graphic intelligence could be equally confronted with the most common linguistic and logical–mathematical intelligences, on which nowadays school tends to focus, and it could complete and enrich the already investigated visual and spatial intelligences. Thinking of the graphic skills as form of intelligence obliges to turn the attention not on the product but on the “cognitive process” that led to the elaboration of that product. This means a change of perspective able to suggest new approaches to teaching at all levels and in all the fields of education.